Trends in Brazilian academic production in the History of Mathematics Education: directions from EBRAPEM - Magalhaes Gomes, Maria Laura; Brito, Arlete de Jesus [UNESP] (Unesp-dept Mathematica, 2009)
The number of papers on History of Mathematics Education presented at EBRAPEM (Brazilian Meeting of Graduate Students in Mathematics Education) has increased significantly between 2003 and 2008. This article presents a study with the aim of identifying themes, periods in focus, and sources and theoretical and methodological references used by the authors of the papers on History of Mathematics Education published in the proceedings of VII, VIII, IX, X, XI and XII EBRAPEM. The study indicates that the approach of ongoing research in History of Mathematics Education in Brazil has been similar to the approach of research in History of Education in general. However, the institutional separation between these two areas of investigation is noted as a factor rendering communication between both groups of researchers difficult.
Keywords: History of Mathematics Education; Encontro Brasileiro de Estudantes de Pos-Graduacao em Educacao Matematica (EBRAPEM)